Long-Term Clinical Behavior of Jejunoileal Involvement in Crohn’s Disease - Hugh J Freeman (Canadian Journal of Gastroenterology)
Diffuse and extensive jejunoileal Crohn's disease is an uncommon entity. In 39 patients, including 21 males and 18 females, followed for a mean duration of over 16 years between 1979 and 2004, the extent of disease was defined and disease behaviour characterized. Over 80% of patients had concomitant colonic and/or gastroduodenal involvement with Crohn's disease, suggesting that this entity may represent a specific clinical phenotype of extensive disease localization. Classification of Crohn's disease behaviour using the Vienna classification schema revealed that virtually all patients in this study suffered from intestinal stricture formation or penetrating disease complications. Moreover, pharmacological therapies with corticosteroids and immunosuppressant drugs were rarely successful, with virtually all patients requiring at least one, and usually multiple, intestinal resections. Finally, most patients required long-term nutritional support, often with home parenteral nutrition. New treatments are required, possibly defined on the basis of their effectiveness in reducing the severity and extent of intestinal disease, rather than more conventional statistically driven reductions in disease activity indexes.